1996
DOI: 10.1159/000150504
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human Cytomegalovirus Immediate-Early Gene Expression

Abstract: The positive and negative cis-acting elements that affect transcription from the human cytomegalovirus major immediate-early (MIE) promoter and the viral and cellular proteins that bind to these elements are discussed. The data obtained using in vitro transcription and transient transfection assays are reviewed and compared to recent data using recombinant viruses with exacting elements deleted. The effects of cell type and cellular differentiation on activation of transcription from the MIE promoter are compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
139
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(144 citation statements)
references
References 38 publications
3
139
0
2
Order By: Relevance
“…We conclude from this observation that a deletion of a large part of the MIERR does not interfere with the ability of PML to inhibit HCMV IE gene expression. Moreover, the deletion of the modulator and distal enhancer region may even augment PML-mediated repression, since the binding of transcription factors that normally antagonize PML-mediated gene silencing might be abrogated (40); this could explain the enhanced repression of AD169/del-MIEP genomes in the presence of PML compared to wt AD169 DNA. A lack of hDaxx, in contrast, only marginally elevated IE transcription of AD169/del-MIEP, indicating that the deleted region of the MIERR contains important target sequences for hDaxx-mediated repression.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude from this observation that a deletion of a large part of the MIERR does not interfere with the ability of PML to inhibit HCMV IE gene expression. Moreover, the deletion of the modulator and distal enhancer region may even augment PML-mediated repression, since the binding of transcription factors that normally antagonize PML-mediated gene silencing might be abrogated (40); this could explain the enhanced repression of AD169/del-MIEP genomes in the presence of PML compared to wt AD169 DNA. A lack of hDaxx, in contrast, only marginally elevated IE transcription of AD169/del-MIEP, indicating that the deleted region of the MIERR contains important target sequences for hDaxx-mediated repression.…”
Section: Discussionmentioning
confidence: 99%
“…MIEP activity is regulated by a myriad of positively and negatively acting cellular and viral proteins. For example, there are numerous nuclear factor-1 (NF-1) sites within the MIEP and the 18 and 19 bp repeat sequences contain NF-kB and cyclic AMPresponsive element binding protein (CREB) binding sites respectively (Meier & Stinski, 1996). Conversely, several studies using non-permissive cells have shown that the modulator and the 21 bp repeats are responsible for the inhibition of MIEP activity in such cells (Nelson et al, 1987;Lubon et al, 1989;Kothari et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…These IE proteins are potent and promiscuous transactivators of both cellular and viral genes, and serve to activate the viral early (E) gene promoters (Pizzorno et al, 1988;Malone et al, 1990), ultimately leading to viral DNA replication, expression of the viral late (L) genes and virus assembly. The expression of IE72 and IE86 is under the control of the major immediate-early promoter (MIEP), a highly complex region comprising a TATA box, an upstream imperfect dyad symmetry element (also termed the modulator), and an extremely powerful enhancer region made up of a series of 17, 18, 19 and 21 bp repeat motifs (reviewed in Meier & Stinski, 1996). MIEP activity is regulated by a myriad of positively and negatively acting cellular and viral proteins.…”
mentioning
confidence: 99%
“…For example, in undifferentiated monocytes, little or no human CMV IE gene products are expressed, and CMV remains latent. Abundant IE gene products are produced and infectious CMV is generated when the monocytes differentiate to macrophages (30). The molecular basis for the repression of CMV IE gene remains largely unknown.…”
mentioning
confidence: 99%